Central Center of Social Representations and the Educational Field - Brito, Carlos Alexandre Felício (Seven Editora, 2023)
The way of apprehending the content of social representations is rescued on two orientations that are not exclusive. The content is treated as a structured field or as a structuring core. The subject who expresses a representation and constructs the real object is imagined and symbolized by its representation(s), in a continuum of (re)modeling. Here the structuring core of the social representations of the field of educational research is revealed, which highlights: Subject-Representations-Object. From the great theory elaborated by Moscovici (2015) emerge complementary theoretical currents. The main theories are those led by Denise Jodelet, Willem Doise and Jean-Claude Abric (focus of this essay). The objectives of this theoretical essay were: i) to present in a synthetic way the basic propositions of the Central Core Theory and ii) to present an experience report using TNC in the educational field. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-131